Using Historical Biogeography Models to Study Color Pattern Evolution. (20th February 2019) - Eliason, Chad M; Andersen, Michael J; Hackett, Shannon J
Abstract: Color is among the most striking features of organisms, varying not only in spectral properties like hue and brightness, but also in where and how it is produced on the body. Different combinations of colors on a bird's body are important in both environmental and social contexts. Previous comparative studies have treated plumage patches individually or derived plumage complexity scores from color measurements across a bird's body. However, these approaches do not consider the multivariate nature of plumages (allowing for plumage to evolve as a whole) or account for interpatch distances. Here, we leverage a rich toolkit used in historical biogeography to assess color pattern evolution in a cosmopolitan radiation of birds, kingfishers (Aves: Alcedinidae). We demonstrate the utility of this approach and test hypotheses about the tempo and mode of color evolution in kingfishers. Our results highlight the importance of considering interpatch distances in understanding macroevolutionary trends in color diversity and demonstrate how historical biogeography models are a useful way to model plumage color pattern evolution. Furthermore, they show that distinct color mechanisms (pigments or structural colors) spread across the body in different ways and at different rates. Specifically, net rates are higher for structural colors than pigment-based colors. Together, our study suggests a role for both development and selection in driving extraordinary color pattern diversity in kingfishers. We anticipate this approach will be useful for modeling other complex phenotypes besides color, such as parasite evolution across the body.